Subgaleal hematoma in hereditary coagulopathy haemophilia B: a case report - Arora, Vivek; Sharma, Kapil; Sharma, Akanksha; Joshi, Mahima (International Journal of Contemporary Pediatrics, 2024)
Subgaleal haemorrhage, characterized by blood accumulation in the subgaleal space, can lead to significant blood loss and shock, often exacerbated by hereditary coagulopathies like haemophilia. A full-term male neonate, born at 39 weeks via spontaneous vaginal delivery, presented 12 hours post-birth with temporal swelling, periorbital edema, and raccoon eyes. Examination showed increased head circumference, severe anaemia, and elevated aPTT. Imaging confirmed subgaleal hematoma. The infant received packed red blood cells, fresh frozen plasma, factor IX, IV fluids, antibiotics, and phototherapy.